Radiation imaging using a compact Compton camera mounted on a crawler robot inside reactor buildings of Fukushima Daiichi Nuclear Power Station. Issue 9 (3rd October 2019) - Sato, Yuki; Terasaka, Yuta; Utsugi, Wataru; Kikuchi, Hiroyuki; Kiyooka, Hideo; Torii, Tatsuo
ABSTRACT: The Fukushima Daiichi Nuclear Power Station (FDNPS), operated by Tokyo Electric Power Company Holdings, Inc., went into meltdown in the aftermath of a large tsunami caused by the Great East Japan Earthquake of 11 March 2011. Measurement of radiation distribution inside the FDNPS buildings is indispensable to execute decommissioning tasks in the reactor buildings. We conducted a radiation imaging experiment inside the reactor building of Unit 1 of FDNPS by using a compact Compton camera mounted on a crawler robot and remotely visualized gamma-rays streaming from deep inside the reactor building. Moreover, we drew a radiation image obtained using the Compton camera onto the three-dimensional (3-D) structural model of the experimental environment created using photogrammetry. In addition, the 3-D model of the real working environment, including the radiation image, was imported into the virtual space of the virtual reality system. These visualization techniques help workers recognize radioactive contamination easily and decrease their own exposure to radiation because the contamination cannot be observed with the naked eye.